Optimized Solid-Phase Extraction of Astaxanthin from Portunus trituberculatus Using Response Surface Methodology and Ionic Liquid-Based Sorbents - Lee, Y.R.; Lee, Y.J.; Row, K.H. (Asian Journal of Chemistry, 2015)
A 17-run Box-Behnken design was used to optimize the extraction conditions of astaxanthin from Portunus trituberculatus. The effects of the extraction time (h), extraction temperature (°C) and liquid to solid ratio were investigated. The following optimal conditions were derived using a response surface methodology: extraction time = 2 h, extraction temperature = 83 °C and ratio of liquid to solid = 10:1. The theoretical amount of astaxanthin (29.34 μg g-1) was obtained under the above conditions using Design-Expert software. The solid-phase extraction method was used to purify astaxanthin from Portunus trituberculatus using ionic liquid-based silica and polymer, such as SilprMImCl, SilprBimCl, SilprNH2, PEImCl, PBImCl and PHImCl sorbents. The optimal solid-phase extraction conditions were water as the washing solvent and ethanol as the elution solvent. Under these conditions, 18.3 μg g-1 astaxanthin was obtained, which was in good agreement with the value predicted from the Box-Behnken design model.